Optimization of Monochloroacetic Acid Biodegradation by Recombinant E. coli BL21 (DE3)/pET-bcfd1 Carrying Haloacid Dehalogenase Gene from Bacillus cereus IndB1 - Enny Ratnaningsih; Rachmad Ade; Rindia Maharani Putri; Idris Idris (Center of Biomass & Renewable Energy, Diponegoro University, 2021)
In recent years, attention to microbial dehalogenase has continually increased due to its potential application, both in bioremediation and in the biosynthesis of fine chemicals. Many microbial recombinant strains carrying dehalogenase gene have been developed, particularly to increase the dehalogenase production and its quality. In this study, we aimed to find the optimum condition for the production of active haloacid dehalogenase by E. coli BL21 (DE3) harboring recombinant plasmid pET-bcfd1 that carried haloacid dehalogenase gene from Bacillus cereus IndB1 local strain. This would be examined by assessing the ability of whole cell life culture to degrade monochloroacetic acid (MCA) and quantifying the chloride ion released into the medium. Several variables were evaluated to find this optimal condition. We found that the best condition for MCA biodegradation using this recombinant clone was at 0.2 mM MCA, 10 μM of isopropyl β-D-1-thiogalactopyranoside (IPTG), 6 hours of pre-induction incubation at 37ºC with shaking, 2 hours IPTG induction at 30ºC with shaking, at pH 7 in Luria Bertani (LB) liquid medium without NaCl, which produced about 0.056 mM chloride ions. Inducer concentration, pre-induction incubation time and temperature, as well as induction time and temperature were apparent to be associated with the expression of the protein, while the MCA concentration and the pH of the medium influenced the ability of the recombinant E. coli BL21 (DE3)/pET-bcfd1 to grow in toxic environment. Our findings laid the foundation for exploration of dehalogenases from local Bacillus strains through genetic engineering for MCA biodegradation